Preparation and characterization of composites from copolymer styrene-butadiene and chicken feathers - Maria Leonor Mendez-Hernandez (Polímeros: Ciência e Tecnologia, 2018)
Over five million tons of chicken feathers (CF) are generated all over the world by the poultry industry, with an immense potential to exploit. Keratin is an abundant protein found in chicken feathers that offers excellent thermal properties and it is durable, insoluble in organic solvents and chemically unreactive. Elastomers are materials with a wide application range, for instance, adhesives, shoe soles, plastic modifiers, tire industry, sealants, among others. However, it is necessary to improve their properties and mechanical performance at elevated temperatures. A good path to do so is to combine the elastomer with CF to obtain materials with enhanced properties. In present work, a composite based on styrene-butadiene (SB) elastomer and CF was prepared by means of melt mixing. Composites were characterized by FTIR, DSC, DMA and X ray diffraction techniques. The results show that there is an increase in stiffness of SB/CF composites compared with pure elastomer.